Non-vitamin K antagonist oral anticoagulants and major bleeding-related fatality in patients with atrial fibrillation and venous thromboembolism : a systematic review and meta-analysis - Caldeira, Daniel (2018)
Copyright © 2015, BMJ Publishing Group Ltd and the British Cardiovascular Society.